Comparison between Gambang residual soil and Bentong residual soil in terms of collapsibility - Wartini, Warni (2009)
Residual soils are products of chemical weathering and thus their characteristics are dependent upon environmental factors of climate, parent material, topography and drainage, and age. Residual soils with extensive weathering of parent materials can yield collapsible soil deposits. Nowadays, most of tragedy that cause by collapsibility of residual soil occurs very extensively, for example the incident at Bukit Antarabangsa which occurred at the end of the year 2008. This tragedy happened because Malaysia is in the tropical climate area and its land is covered by more than 80 percent of residual granite and sedimentary rock soil. These types of soil have high possibility to collapse when wetted. The purpose of this study is to examine the collapsibility of Gambang residual soil in Pahang area, which is compared with Bentong residual soil in terms of collapsibility. The oedometer consolidation test is used to determine the consolidation parameters of soil. The testing give result both the residual soil in Gambang and Bentong have significant different on collapse potential. The influence of the particle size distribution, void ratio and density on the collapsibility of soil also has been compared. Determination of collapsibility of residual soil will be one of the best implementation and important in the future.